ANALISIS POLA RITMIS PADA LAGU 'LIHAT KEBUNKU' - Sesy Nugraha; Resa Respat; Pidi Mohamad Setiadi (STKIP Subang, 2025)
This study aims to analyze the characteristics of rhythmic motif patterns in the children’s song Lihat Kebunku and to examine their meaningfulness in the context of elementary school music learning. A qualitative approach with content analysis was employed by examining the song’s score and lyrics. The results indicate that the rhythmic patterns are dominated by consistent and repetitive motifs across the antecedent and consequent phrases, facilitating children’s memorization and active participation during learning activities. No significant musical techniques such as diminution, augmentation, or retrograde were found, reflecting a simple rhythmic structure appropriate for the cognitive development of elementary school children. These findings align with previous research highlighting the important role of rhythmic patterns in enhancing children's creativity and musical abilities. Therefore, the rhythmic motif patterns in Lihat Kebunku can serve as a reliable basis for developing effective and enjoyable music teaching materials for elementary education.